VISUAL AESTHETICS OF ELEMENTARY SCHOOL STUDENTSâ€™ â€œBATIKâ€ DESIGN - Probosiwi, Probosiwi; Gusnanda, Koko (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
This paper describes the beauty of layout in the process of making